PEOPLE MANAGEMENT IN EDUCATION: an analysis of participatory proposals in the development of public educational policies (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of this paper is to address the management of people in education, which has not yet become an effective practice in schools, the administrative hierarchy, the prevailing management rules, most often not shared with all teaching staff. To develop the theoretical framework used is a bibliography of books and articles whose topics were: management education and school management, people management and a participatory approach in school articulation strategies in the management of people who will support the school effectively. In conclusion, it was possible to understand how people management can strengthen education in the school and achieve success plan, articulating the extent of people management in a participatory and strategic approach which will support the strategic use this strengthening intentional. Keywords: management, people, education, democracy.